High-fat feeding induces mobilization of vitamin C in obese prone rats. (August 2018) - Tranberg, B.; Hellgren, L.I.; Lykkesfeldt, J.; Hansen, A.K.
Abstract: In obesity and dyslipidemia, hydrolysis of triacylglycerol (TAG) into non-esterified fatty acids (NEFAs) may contribute to insulin resistance, and production of oxygenated, bioactive polyunsaturated fatty acids may increase oxidative stress. Here we show that after six weeks of high-fat feeding of obese prone rats (Crl:OP(CD), vitamin C was increased both in liver (P < 0.01) and plasma (P < 0.001), while both TAG (P < 0.01) and NEFA (P < 0.001) were lower than in low-fat fed control rats. Hepatic vitamin C biosynthesis was similar between groups, indicating that a new steady state level was established with a higher vitamin C level adequate for supplying the systemic needs. Glucose and insulin sensitivity were unaffected at this stage. Eventually, the mobilization of vitamin C may be seen as a mechanism to protect the host against insulin resistance. Highlights: High-fat feeding increases vitamin C in both liver and plasma of obese prone rats in accordance with observations in mice This is not accompanied by an increased vitamin C biosynthesis in contrast to observations in mice Glucose and insulin sensitivity is unaffected at this stage